2015
DOI: 10.1007/s12035-015-9543-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Drug Artemether Inhibits Neuroinflammation in BV2 Microglia Through Nrf2-Dependent Mechanisms

Abstract: Artemether, a lipid-soluble derivative of artemisinin has been reported to possess anti-inflammatory properties. In this study, we have investigated the molecular mechanisms involved in the inhibition of neuroinflammation by the drug. The effects of artemether on neuroinflammation-mediated HT22 neuronal toxicity were also investigated in a BV2 microglia/HT22 neuron co-culture. To investigate effects on neuroinflammation, we used LPS-stimulated BV2 microglia treated with artemether (5-40µM) for 24 hours. ELISAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 44 publications
4
60
0
2
Order By: Relevance
“…Our present study here further supported the antioxidant effects of artemisinin and indicated the possibility that artemisinin administration might be a potential therapeutic strategy for the treatment of AD. Biologically, it has been found that artemisinin-mediated neuroprotection against neuronal apoptosis is regulated by several pathways including ERK1/2, p38MAPK and Nrf2/HO-1 survival/apoptotic signaling pathway [17,19,21,35]. Our results provided mechanistic evidences to support that artemisinin protected PC12 cells from H 2 O 2 -induced oxidative damage via p38MAPK activation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our present study here further supported the antioxidant effects of artemisinin and indicated the possibility that artemisinin administration might be a potential therapeutic strategy for the treatment of AD. Biologically, it has been found that artemisinin-mediated neuroprotection against neuronal apoptosis is regulated by several pathways including ERK1/2, p38MAPK and Nrf2/HO-1 survival/apoptotic signaling pathway [17,19,21,35]. Our results provided mechanistic evidences to support that artemisinin protected PC12 cells from H 2 O 2 -induced oxidative damage via p38MAPK activation.…”
Section: Discussionsupporting
confidence: 65%
“…In clinical relevance, artemisinin is among the most effective therapies for malaria with great safety and the preferred first-line treatment for the disease [15]. Beside these effects, previous studies including some from our group, have shown that artemisinin and its derivatives have neuroprotective effects suggesting that artemisinin might be potential candidate for AD therapy [16][17][18][19]. It has been recognized that artemisinin-mediated neuroprotection against neuronal apoptosis from various insults is regulated by ERK1/2 survival/apoptotic signaling pathway rather than the Akt pathway [16,18,19].…”
Section: Introductionmentioning
confidence: 94%
“…Firstly, artemether, a lipid-soluble derivative of artemisinin has been reported to possess anti-inflammatory properties by activated Nrf2 activity [16]. As we know, neuroinflammation played a major role in the formation of Aβ; besides, activated Nrf2 activity also shows benefits to AD in reports [42].…”
Section: Discussionmentioning
confidence: 99%
“…At present, artemisinins are among the most effective therapies for malaria with great safety and the preferred first-line treatment for the disease [15]. Except these effects, accumulated studies indicate that artemisinin and its derivatives have neuroprotective effect, therefore be potential candidates for treatment of AD [16], [17], [18]. Artemisinin easily penetrate the blood–brain barrier and we have previously showed that artemisinin was able to protect PC12 cells and cortical neurons from free radical/oxidative stress induced by hydrogen peroxide and sodium nitroprusside (SNP) [17], [19].…”
Section: Introductionmentioning
confidence: 99%
“…2.11 | NF-κB DNA binding assay NF-κB DNA binding assay was carried out as earlier described (Okorji, Velagapudi, El-Bakoush, Fiebich, & Olajide, 2016). DNA binding assay was carried on nuclear extracts using the TransAM NF-κB transcription factor EMSA kit (Activ Motif, Belgium), which employs a 96-well plate to which an oligonucleotide containing the NF-κB consensus site (5′GGGACTTTCC-3′) has been immobilized.…”
Section: Nf-κb Reporter Gene Assaymentioning
confidence: 99%